Unfolding choices in digital writing: A functional perspective on the language of academic revisions - Bowen, Neil (Journal of Writing Research, 2019)
To date, research into functional descriptions of unfolding language has been almost entirely focused on speech. And whilst writing research has examined the revision of language units, it has backgrounded how these revisions contribute to the unfolding of a text’s meanings. Therefore, using Systemic Functional Linguistics (SFL) as an underlying framework, and keystroke logging software (Inputlog) as a data collection tool, this paper takes a first step toward a dynamic description of written text in terms of the language structures, functions, and systemic choices found in the written revisions of two 2nd year UK undergraduates. More specifically, in detailed textual analysis of four unfolding, digitally composed text, whose end products totalled approximately 1700 words, this paper focuses on the revisions made during consecutive writing sessions, which lasted anything from 8mins to 8hrs 37mins and totalled 56hrs 18mins of recordings. The findings suggest that certain language choices may play a key role when it comes to shaping academic essays, and it is proposed that this new model of analysis can provide an additional perspective on writing behaviour in terms of how meaning-making practices unfold in real time.